Proceso atención de enfermería aplicado en paciente de 29 años de edad con colelitiasis. - Peñafiel Icaza, Joselyn Marioli (2024)
The ·onset of intense pain, typically localized in the right hypochondrium and radiating to the lumbar region, is a common clinical presentation in patients with cholelithiasis. This condition necessitates thorough monitoring and assessment by nursing staff. The aim of this study was· to develop a nursing care process for a female patient with cholelithiasis, utilizing nursing diagnosis. During the study, a care plan was implemented, allowing nursing staff to demonstrate their skills and knowledge in the direct care of the patient, leading to clinical improvement. At the conclusion of the clinical· case study, the set objectives were achieved, which included identifying clinical manifestations, determining the patient's needs based on history, physical examination, and the analysis of functional· patterns, as well as establishing nursing interventions based on the patient’s needs and using NANDA, NOC, and NIC taxonomy.